IDENTIFYING PRIORITY DOMAINS OF CLINICAL LEADERSHIP COMPETENCY AMONG NURSING PROFESSION STUDENTS: IMPLICATIONS FOR NURSING EDUCATION - Contriana Yusinta Bere; Catharina Dwiana Wijayanti (Jurnal Ilmiah Keperawatan, 2026)
Background: Being a key competency for nurses to deliver quality care to patients, clinical leadership is important for providing safe, high-quality, and patient-centered care. Nonetheless, information on the clinical leadership competencies specific to domains for nursing profession students has been scanty, especially in Indonesia. Purpose: The purpose of this research is to ascertain the priority domains of competencies in clinical leadership among students of the nursing profession through CLCF and explore its implications in nursing education. Methods: In the current research, a quantitative descriptive study with a cross-sectional design was carried out on 123 students of nursing profession in Jakarta, Indonesia, employing total sampling technique. Competence of clinical leadership was measured through 40 items Clinical Leadership Competency Framework (CLCF) which is made up of five domains. These domains include; Demonstrating Personal Qualities, Working with Others, Managing Services, Improving Services, and Setting Direction. Results: The nursing students demonstrated moderate proficiency in the aspect of clinical leadership. The mean scores for the five domains of CLCF ranged from 2.33 to 2.67; the mean score of 2.67 was achieved in the domain of Managing Services, while 2.65 in Demonstrating Personal Qualities, 2.59 in Working with Others, 2.56 in Improving Services, and 2.33 in Setting Direction. None of the subjects demonstrated high proficiency in all five domains. Conclusion: Clinical leadership proficiency is uneven in different domains and therefore calls for more emphasis on strategic leadership education. It would be useful to develop competencies in the aspect of Setting Direction through leadership learning and competency-based education.